Prospective hospital based study on persistent diarrhoea. Issue 7 (July 1991) - Dutta, P; Lahiri, M; Sen, D; Pal, S C
Abstract : A total of 383 children aged less than 5 years suffering from acute watery diarrhoea or dysentery were studied in hospital to determine the rate of persistent diarrhoea. Altogether 335 (87.5%) recovered within 13 days. Only in 48 (12.5%) did the diarrhoea continue for 14 days or more, and they were considered as having persistent diarrhoea. Children aged between 7 and 18 months had a significantly increased incidence of persistent diarrhoea. Children suffering from grade II-IV malnutrition constituted the majority (70.8%) of those with persistent diarrhoea. Higher rates of isolation of Shigella flexneri, Shigella dysenteriae 1, and Salmonella typhimurium were observed among patients with persistent diarrhoea than in those with diarrhoea of shorter duration. No positive correlations were observed between the clinical severity of disease at hospital admission and measles. Breast fed babies were not prone to persistent diarrhoea.